Halal Tourism Development Strategy in Loang Baloq Beach, Mataram City - Putri, Risma Sahrani; Yanti Sandra Dewi, Novi; Agustina, Ahadiah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Halal tourism is currently a new concern in the tourism industry because its growth has increased significantly. The main problem of this research is how the policy direction of the strategy, the implementation of policy direction in the development of halal tourism in Loang Baloq, and the inhibiting factors in implementing the halal tourism development strategy in Loang Baloq Beach. This study aims to find out how the management strategy in developing halal tourism in Loang Baloq. This study uses the descriptive qualitative research method, which is a study that seeks to obtain complete information to obtain information The observation and interview process is very important in data collection. From observations and interviews, it is expected to be able to explore the problems that exist in the development of halal tourism in Loang Baloq Beach to find out what strategies can be done to develop Loang Baloq Beach tourism in the eyes of local and National as well as in the welfare of local communities. Halal tourism development strategy in Loang Baloq. This includes increasing visitor comfort, and creating a friendly and friendly environment supported by (1) the development of halal tourist destinations including the development of halal tourism objects and the improvement of the development of halal tourism facilities and infrastructure (2) developing the Halal Tourism Industry Program including the development of the halal industry and halal facilities such as halal certificates.